Work Life Balance among Female School Teachers Delivering Online Curriculum During COVID-19 - Jayant Sahoo Kumar; Vijay Prakash (Indonesian Journal of Multidisciplinary Science, 2023)
With recognize to emerging nations, issues of work life balance among female in the education sector are not well researched. Increased female employment has led to a swelling interest from academia and industry on WLB. With higher access to better educational opportunities, growing number of female are coming into the workforce, and moving from being home-makers to the geared up work force, thereby necessitating an urgent need to observe this phenomenon. Carrying on with on line lessons remotely has grow to be the order of the day, and it is turning into worrying when each school and personal life operate from the same space. The predominant idea here is to recognize challenges at some point of COVID which are being confronted with the aid of school teachers in Bandgaon block delivering content to students from home and their surviving strategies. A combination of 150 fermale teachers responses from primary, secondary and high school are covered in the study. Average literacy rate of Bandgaon Block in 2011 had been 54.46 in which, man and female literacy had been 69.02 and 39.95 respectively. Total literate in Bandgaon Block have been 805 of which man and woman have been 547 an 258 respectively. This study also identifies primary problems and challenges which confronted by unwedded and wedded working female in the course of Covid-19. Both Telephonic  and Online interview  are taken to fulfill the objectives. Random sampling technique used to be used for collection of primary data through Telephinic  and Online interviews.